1992
DOI: 10.1007/bf00171969
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biofilm populations of Nitrosomonas europaea

Abstract: The influence of surface attachment and growth on inhibition of the ammonia oxidizing bacterium, Nitrosomonas europaea, by nitrapyrin was investigated in liquid culture in the presence and absence of glass slides. Significant attachment to glass slides occurred in the absence of ammonia, but the extent of attachment was not affected by nitrapyrin, nor by previous culture of cells in medium containing nitrapyrin. The presence of glass slides affected neither the specific growth rate of N. europaea, measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In soil, where majority of particles are negatively charged and cells of nitrite-oxidizing bacteria may be less firmly attached than those of ammonia-oxidizing bacteria (Prosser, 1989). Clay minerals strongly adsorb ammonium ions, resulting in preferential colonization of such surfaces by ammonia-oxidizing bacteria which, however, realize reduced growth rate due to localized depletion of ammonia at the surface (Powell and Prosser, 1992). Although the concentration of ammonia adsorbed to clay minerals offers the potential for increased rates of ammonia oxidation, it may be counteracted by localized increases in H + concentration at the same anionic site (Prosser, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In soil, where majority of particles are negatively charged and cells of nitrite-oxidizing bacteria may be less firmly attached than those of ammonia-oxidizing bacteria (Prosser, 1989). Clay minerals strongly adsorb ammonium ions, resulting in preferential colonization of such surfaces by ammonia-oxidizing bacteria which, however, realize reduced growth rate due to localized depletion of ammonia at the surface (Powell and Prosser, 1992). Although the concentration of ammonia adsorbed to clay minerals offers the potential for increased rates of ammonia oxidation, it may be counteracted by localized increases in H + concentration at the same anionic site (Prosser, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…europaea has been examined under different growth states to study inhibition of NH 3 oxidation (Chandran and Love, 2008;Radniecki et al, 2009). A study of N. europaea biofilms reported that established biofilms were less inhibited by the nitrification inhibitor nitrapyrin and exhibited reduced growth rates compared to suspended cells (Powell and Prosser, 1992). Additionally, exponential cells of N. europaea exhibited greater inhibition of NH 3 oxidation when exposed to nitrapyrin compared to stationary-phase cultures (Powell and Prosser, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared with the water column of aquatic environments, solid-phase habitats, such as sediment, particulate material, and aquatic macrophytes, seemed to be differently (35,40,50) and more densely populated with nitrifying bacteria (12,33,34). This surface-attached growth has been proposed to offer resilience against environmental constraints (41). Moreover, the formation of a biofilm on surfaces provides significant benefits for AOB of the Nitrosomonas lineages that are able to produce extracellular polymeric materials.…”
mentioning
confidence: 99%